Development of hazard- and amplification-consistent elastic design spectra. Issue 126 (November 2019) - Poggi, Valerio; Edwards, Benjamin; Fäh, Donat
Abstract: In the framework of the definition of a new building code for dams, the Swiss Federal Office for Energy (SFOE) has commissioned a study on the effect of site response variability on elastic design spectra for different soil conditions and seismic hazard scenarios. The goal of the study presented herein is the definition of a new set of site-dependent design spectra for horizontal and vertical ground-motion, whose design shape (scaled to peak ground acceleration) is to be compared with the present Swiss normative (SIA261, revision 2014) [43]. To accomplish the task, we have created a large dataset of Fourier-domain seismic amplification functions by collecting empirical observations and site-specific ground motion models from both measured and stochastically generated velocity profiles. Fourier spectra were then converted to response spectral amplification using a combination of spectral modeling techniques and random vibration theory. Average amplification models are thus derived for different soil classes (SIA class A–E), according to the Swiss building code provisions, and for a set of magnitude-distance combinations chosen as representative of the Swiss hazard disaggregation scenario at the Sion site in Switzerland. Finally, the response spectral amplification functions from the database have been combined with the normalized uniform hazard spectra computed at Sion for return periods of 500, 1000, 5000 and 10, 000 years. Based on those results, a new set of design spectral shapes is proposed for the different SIA soil classes, accounting for investigated scenario variability and including a reasoned level of conservatism dependent on the distribution of the site-specific amplification models. The proposed methodology targets the reduction in uncertainty associated with seismic design and, although originally focused and applied to the Swiss norm, it could be potentially applied to any national seismic code as a tool for developing, updating or benchmarking the current provisions in a holistic framework. Highlights: Definition of site-dependent design spectra for horizontal and vertical ground-motion. A database of empirical and modeled seismic amplification functions. Seismic hazard through disaggregation scenarios and uniform hazard spectra. Mapping epistemic uncertainty in site response associated with seismic design. A tool for developing, updating or benchmarking the current provisions.